2007
DOI: 10.1002/anie.200701727
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(IV) Alkylidenes as Precatalysts for Direct Arylations of Alkenes with Aryl Chlorides and an Application to Sequential Catalysis

Abstract: Jack of all trades? A ruthenium(IV) carbene complex catalyzes the diastereoselective direct arylation of alkenes using aryl chlorides with high efficiency, which sets the stage for the development of a direct arylation–hydrosilylation sequence (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(60 citation statements)
references
References 35 publications
3
57
0
Order By: Relevance
“…(5)]. The stereochemical outcome is in agreement with a mechanistic proposal that the reaction proceeds by the 2-pyridyl group directed C À H bond activation of olefins, which is in contrast with the Heck-type route that will lead to the E-isomeric product as demonstrated by Inoue and co-workers and Ackermann et al [27] It was also found that the Z double bond of 13 was isomerized during the course of the reaction to the E-isomer 11 [Eq. (6)].…”
supporting
confidence: 87%
“…(5)]. The stereochemical outcome is in agreement with a mechanistic proposal that the reaction proceeds by the 2-pyridyl group directed C À H bond activation of olefins, which is in contrast with the Heck-type route that will lead to the E-isomeric product as demonstrated by Inoue and co-workers and Ackermann et al [27] It was also found that the Z double bond of 13 was isomerized during the course of the reaction to the E-isomer 11 [Eq. (6)].…”
supporting
confidence: 87%
“…Notably, this strategy allowed for the atom-economical synthesis of fully substituted 1,2,3-triazoles in a highly regioselective fashion [54,67]. While the research groups of Rutjes [68] as well as Sharpless [69] elegantly devised alternative approaches exploiting 1-haloalkynes [70], we became interested in exploring a single [7173] inexpensive copper catalyst for one-pot reaction sequences comprising a 1,3-dipolar cycloaddition along with an intramolecular C–H bond arylation; in particular, because of the notable biological activities exerted by fully substituted 1,2,3-triazoles [7488]. As a consequence, we wish to present herein novel cascade reactions, in which cost-effective copper(I) compounds serve as the catalyst for two mechanistically distinct transformations for the synthesis of fully substituted annulated 1,2,3-triazoles as well as for twofold N–H/C–H bond arylations.…”
Section: Introductionmentioning
confidence: 99%
“…[1] For more efficient and greener methods to construct CÀC bonds, much attention has been paid to direct CÀH functionalization, starting from arenes (Scheme 1 A), in the past several decades. [2] Among these modern couplings, the coupling partners can be organic halides/pseudohalides, [3] organometallic reagents, [4] and even another arene. [5] Carboxylic acids are considered another important carbon source because of its ready availability, stability, and nontoxicity.…”
mentioning
confidence: 99%